Murals as Memorials - Bridget Blankley (User Experience & Urban Creativity)
This paper, short though it is, represents my first thoughts on the overlap between street art as memoria and the concept of the artist as implicated subject. That is should we consider the artist who create memorial graffiti as documenters of societies memories or creators of them. In examining the extent to which the making of such art can be considered as an act of shaping rather than reflecting cultural memory I will seek to establish that the artist promotes interaction with both their art and the subject of that art.